Smells like politics: planning and the inconvenient politics of intensive peri‐urban agriculture. (26th December 2017) - Butt, Andrew; Taylor, Elizabeth
Abstract: Intensive farming is an increasing part of Australian agriculture, including in the multi‐functional landscapes at the edges of Australian cities. The example of intensive "broiler" poultry production reveals the tensions that arise when sites of hyper‐productivity conflict with social change in rural areas. Planning processes for intensive farming in the Australian state of Victoria are predicated on stability and consensus: on assumed static and uncontroversial ideas of agriculture, its place, and the primacy of agricultural productivity. Yet concerns about the industrialisation of agriculture are live political issues at the local level, especially in dynamic peri‐urban locations. This paper explores the emergence of a politics of place outside the bounds of planning consensus through an analysis of planning appeals and associated media relating to planning permits for intensive poultry developments in Victoria over 2011–2016. We highlight tensions that exist in relation to technical planning assessments and categorisations used to assert farming as the orthodox use of rural land, especially when new forms of farming look and feel demonstrably different. Using Mouffe's problematising of the negation of antagonism and Rancière's notion of the risks of a false consensus democracy, we argue that planning processes for intensive farming illustrate critical issues in participatory planning. While ostensibly post‐political decision‐making narrows the politics of place and food systems to decisions about policing the boundaries and buffer distances placed around intensive poultry developments, alternative representations of rural life persist. The certainty offered by code‐based planning does not negate the ongoing (if inconvenient) politics of intensive peri‐urban agriculture.